A comparison of the Doppler ultrasound interpretation by student and registered podiatrists - Young, Maria (BioMed Central, 2013)
BACKGROUND: Hand held Doppler ultrasound machines are routinely used by podiatrists to assess the arterial perfusion of the lower limb. They are practical, painless and effective as a screening tool, and the available general evidence would suggest that interpretation by practitioners is reliable. This study compared the abilities of student and Health and Care Professions Council (HCPC) registered podiatrists to identify correctly Doppler ultrasound outputs. METHOD: A prospective single blind comparative study design was utilised. Fifteen Doppler recordings of the blood flow in the posterior tibial artery, five each of monophasic, biphasic and triphasic blood flow, were used to compare the interpretation abilities of 30 undergraduate podiatry students and 30 HCPC registered podiatrists. Chi-squared analysis of the results was undertaken. RESULTS: Chi-squared analysis found that there was no statistically significant difference between the overall abilities of student podiatrists and HCPC registered podiatrists to identify correctly Doppler ultrasound recordings (p = 0.285). No significant difference was found in their ability to identify Doppler ultrasound recordings of monophasic, biphasic or triphasic blood flow (p > 0.050). CONCLUSION: The results of this relatively small study suggest that both student and HCPC registered podiatrists are in general able to identify the nature of blood flow based on the output of handheld Doppler ultrasound units. However, the results raise an issue regarding professional development of practitioners who might have been expected to have enhanced their skills of Doppler ultrasound sound identification since professional registration.